Characterisation of breast cancer infiltrates using monoclonal antibodies to human leucocyte antigens. - Rowe, D; Beverley, P (1984)
Serial frozen sections from eleven patients with malignant breast tumours and five patients with benign disease were studied by indirect immunoperoxidase using a panel of mouse monoclonal antibodies to human leucocyte antigens. More infiltrating leucocytes were seen in tumour sections than those of benign conditions. A considerable proportion of the infiltrating cells were T cells, and more of these were of the suppressor/cytotoxic subset than the helper/inducer subset. The T cells were apparently not all activated as indicated by lower levels of staining with anti HLA-DR than anti-leucocyte antibody. Diffuse staining was sometimes seen with HLA-DR and T cell subset antibodies. Tumour cells did not stain or were only very weakly positive with anti HLA-A, B, C.